Citizen Charter: Terobosan Baru dalam Penyelenggaran Layanan Publik - Dt. Maani, Karjuni (Fakultas Ilmu Sosial Universitas Negeri Padang, 2010)
ABSTRACT Citizen Charter or public service contract is a new strategy in providing services to reach the values of participative, accountable, transparent and collaborative in public service. We know that implementation of public service contract in Indonesia is not understood by local policy maker yet. But, many local governments have successfully implemented contract of public service. It means that public service contract can be tool of creating public service mechanism better and it can be instrument to reform public bureaucracy in Indonesia. Citizen Charter is according to idea of good governance, so governance principles is collaborate of three sector in public service, such as local government, private sector and society. Kata Kunci: Citizen Charter, Public Service, Good Governance